Smoking during Pregnancy and Maternal and Neonatal Complications in Mashhad, Suburbs, and Subsidiary Villages: A Population-based Cross-Sectional Study - mahdi talebi; Veda Vakili; Zahra Abbasi Shaye; Mahmoud Velayati (Mashhad University of Medical Sciences, 2020)
Background: Smoking is very important during pregnancy because of severe fetal and maternal complications. No community-based studies have been conducted on pregnant women in Iran. This study aimed to investigate the prevalence of smoking during pregnancy, as well as maternal and neonatal complications in Mashhad, Iran, during 2017.Methods: This cross-sectional study reviewed the information of 1140 and 92,225 smoking and non-smoking pregnant women during pregnancy, respectively, and 3-5 days after delivery using Sina Electronic Health Record System in Mashhad, Iran, during 2017. All data were extracted, encoded, and entered into SPSS software (version 16).Results: Out of the total of 93,365 pregnant women with a mean age of 22.36 years, the prevalence of smoking during pregnancy was significantly higher among those who live in the city (i.e., Mashhad), compared to individuals living in the suburbs or villages. The mean rates of stillbirth, prematurity, very-low-birth-weight, and low-birth-weight were higher in smoking pregnant mothers, compared to non-smoking ones (p <0.0001). The prevalence of smoking among literate and employed pregnant mothers was significantly higher than illiterate and unemployed pregnant women (p <0.0001). The mean birth weight of newborns of smoking mothers (1528gr) was less than the half mean of the birth weight (3180gr) of newborns of non-smoking mothers (p <0.0001).Conclusion: The prevalence of smoking in mothers living in Mashhad, Iran, was 1.2%, which is less than the global average. The results of this study showed that smoking during pregnancy has many maternal and fetal complications.